Control of the growth of Alicyclobacillus acidoterrestris in industrialized orange juice using rosemary essential oil and nisin. (1st January 2021) - da Silva, D.A.M.; Fernandes, M.S.; Endo, E.H.; Vital, A.C.P.; Britta, E.A.; Favero, M.E.; Castro, J.C.; Matumoto‐Pintro, P.T.; Dias Filho, B.P.; Nakamura, C.V.; Machinski Junior, M.; Mikcha, J.M.G.; et al.
Abstract: The use of rosemary essential oil (RO) and its combination with nisin (RO+N) in preventing the multiplication of Alicyclobacillus acidoterrestris in orange juice was evaluated. The minimum inhibitory and bactericidal concentrations (MIC and MBC) for RO were both 125 μg ml −1 while RO+N displayed a synergistic effect. The use of RO and RO+N at concentrations of 1, 4 and 8× MIC in orange juice for 96 h was evaluated in terms of their sporicidal effectiveness. With regard to the action against A. acidoterrestris spores, RO at 8× MIC was sporostatic, whereas RO+N at 1× MIC was sporicidal. Morphological changes in the structure of the micro‐organism after treatment were also observed by microscopy. Furthermore, flow cytometric analysis showed that most cells were damaged or killed after treatment. In general, the antioxidant activity after addition of RO+N decreased with time. The results demonstrate that using the combination of RO and nisin can prevent the A. acidoterrestris growth in orange juice. Significance and Impact of the Study : Alicyclobacillus sp. are responsible for the deterioration of orange juice, mainly due to their capacity to form spores. In the search for new control alternatives, this study evaluated the antimicrobial activity of rosemary essential oil and its combination with nisin against the vegetative cells and spores of Alicyclobacillus acidoterrestris in orange juice. The phenolic compound content and antioxidant activity of orange juice were also evaluated after the addition of these compounds. Rosemary oil, when associated with nisin, resulted in a sporicidal effect, thus demonstrating its potential application in the prevention of Alicyclobacillus sp. in orange juice.